2004
DOI: 10.1080/02699050310001646107
|View full text |Cite
|
Sign up to set email alerts
|

Interview study of the effects of paediatric traumatic brain injury on memory

Abstract: Memory loss is common and can impact on everyday living, but is selective in the types of memory affected. Follow-ups are recommended to assess quantitatively, the so-far, little-known effects of paediatric TBI on prospective memory and to examine more closely parent interventions to assess their wider applicability in TBI rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Implications: There is now more evidence that PM is a common sequelae of childhood severe TBI 6,12,13 , that can persist over time. When assessing sequelae post TBI, the evaluation should include an assessment of PM in addition to classical episodic memory assessment, especially in legal expertise in order not to underestimate memory impairment in daily life.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Implications: There is now more evidence that PM is a common sequelae of childhood severe TBI 6,12,13 , that can persist over time. When assessing sequelae post TBI, the evaluation should include an assessment of PM in addition to classical episodic memory assessment, especially in legal expertise in order not to underestimate memory impairment in daily life.…”
Section: Resultsmentioning
confidence: 99%
“…Although PM problems are reported as a major concern by the parents of children with traumatic brain injury (TBI) 6 , there are surprisingly few studies that have evaluated PM in children with TBI (as opposed to adults with TBI 3,7,8 ). Ward et al 9 found that children with TBI had poorer PM than their uninjured peers, and that this may be attributable to worse executive functioning, especially if the PM task is cognitively demanding.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Everyday life for children and adults alike is replete with instrumental activities, such as PM tasks, to the extent that PM is an essential ability to effectively manage the challenges of daily living (Harris, 1984;Meacham and Dumitru, 1976;Winograd, 1988). Neurologic insults such as traumatic brain injury (TBI) have been shown to result in impairments of PM performance in adults (Cockburn, 1995;Fortin et al, 2002;Groot et al, 2002;Hannon et al, 1995;Henry et al, 2007;Kinsella et al, 1996;Kliegel et al, 2004;Knight et al, 2005Knight et al, , 2006Louda et al, 2007;Mathias and Mansfield, 2005;Roche et al, 2002Roche et al, , 2007Shum et al, 1999) and children (McCauley and Levin, 2004;McCauley et al, 2009McCauley et al, , 2010aWard et al, 2004Ward et al, , 2007. Although brainbehavior relations of episodic (i.e., retrospective) memory have been frequently studied in children with TBI (Anderson and Catroppa, 2007;Catroppa and Anderson, 2002;Catroppa et al, 2008;Di Stefano et al, 2000;Donders, 1993;Donders and Hoffman, 2002;Lowther and Mayfield, 2004;Roman et al, 1998;Salorio et al, 2005), little corresponding neuroimaging data currently exists concerning PM functioning in children and adolescents with TBI.…”
Section: Introductionmentioning
confidence: 98%
“…Impairments in these components of attention have been commonly found following child acquired brain insult (ABI) [2,7,[21][22][23][24][25]. The memory system is also complex and incorporates immediate, short-term memory and multi-trial learning [1,[26][27][28][29][30][31]; prospective memory [32,33]; explicit memory [34,35]; metamemory [36,37] and working memory [38,39], with deficits in these skills reported in the context of child ABI.…”
Section: Introductionmentioning
confidence: 97%